(untitled) (DARYAFT, 2023)
Literary history of any nation is influenced by its literary tendencies, linguistic attitudes and thoughts, because literature is born of political, social, moral, religious, historical, linguistic, civilization and culture. Literary texts also help in the ideological formation of literary history. Literary criticism has played a pivotal role in interpreting, understanding and determining the status of literary texts. Thus, the theoretical construction of literature in literature has been the function of literary criticism. The theories of Urdu literary history that have been created have been taken in the light of the intellectual and ideological views of literary historians and the researcher and critical analysis and commentaries of critics. At the same time, new concepts have emerged. Under these modern concepts, literature is not just a field study, but a literary creation and the social sciences of the creator’s era, including political, socio-economic, cultural, psychological, moral and religious sciences and arts. An interpretation of these collections of histories based on the interactions of thoughts, feelings and emotions that take place in human life under the influence of Contains behavioral studies. Urdu literary history has different views in its footsteps, various theories and ideas about literary history have been expressed.